Using the Clinical Global Impression scale to assess social communication change in minimally verbal children with autism spectrum disorder. Issue 2 (19th November 2021) - Toolan, Christina; Holbrook, Alison; Schlink, Andrew; Shire, Stephanie; Brady, Nancy; Kasari, Connie
Abstract: Assessing improvements in social communication behaviors in minimally verbal children with autism spectrum disorder (ASD) is often challenging. The Clinical Global Impression Scale (CGI) is a 7‐point scale that has been adapted so that clinicians can easily and quickly rate social communication behaviors. The current study evaluated the CGI‐Improvement (CGI‐I) subscale as a measure of social communication change in minimally verbal children with ASD. The sample included 54 minimally verbal school‐age children with ASD enrolled in a social communication intervention trial. CGIs were rated by interventionists and the study coordinator at baseline and at Week 6 of intervention, and were compared to scores on the Communication Complexity Scale (CCS). Results indicated that CGI ratings corresponded with CCS scores at baseline and Week 6. Children who were rated as more severe on social communication at baseline demonstrated lower complexity of communication compared to those who were rated as less severe. Those who demonstrated fast response to intervention at Week 6 showed greater improvement in their joint attention than those who were slower responders. These results provide support for the utility and validity of the CGI‐I as a measure of social communication change in minimally verbal children. This study tested the CGI, a clinician rating scale, with a group of children with ASD with limited language who received intervention to improve social interactions and communication. Children's CGI ratings were comparable to other assessments in measuring social communication. The CGI may be a useful tool for those interested in quickly and easily tracking changes in children's social communication over the course of treatment. Lay summary: This study tested the Clinical Global Impression (CGI), a clinician rating scale, with a group of children with ASD with limited language who received intervention to improve social interactions and communication. Children's CGI ratings were comparable to other assessments in measuring social communication. The CGI may be a useful tool for those interested in quickly and easily tracking changes in children's social communication over the course of treatment.